High-spin states and rotational coexistence in 25Mg - Headly, D. M.; Sheline, R. K.; Tabor, S. L.; Huttmeier, U. J.; Gross, C. J.; Moore, E. F.; Wildenthal, B. H.; Weller, H. R.; Whitton, R. M.; Ragnarsson, I. (Physics Letters B, 1987)
New high spin states in 25Mg have been located above the neutron threshold using the 12C(14N, pγ)25Mg reaction at E=23.5 MeV. The members of the ground state rotational band (Kπ= 5 2+ have been tentatively identified up to 15 2+. The yrast 15 2+ (not a member of the ground state band) and 17 2+ states have also been tentatively assigned. These results support the interpretation of the new 17 2+ state and the previously known yrast 13 2+ state as fully aligned prolate configurations, i.e., prolate particle-hole states with K=I and γ=-120°.